ANALYSIS OF SOUND ERRORS IN READING THE QUR'AN TPA AL-HAMZAH MAKASSAR STUDENTS (PHONOLOGY LEARNING) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research aims to analyze the sound errors made by TPA Al-Hamzah Makassar students when they carry out reading activities. This research uses descriptive qualitative analysis method. To collect research data, the method used is the method of observation, interviews, documentation and recording. The results of this study indicate that the forms of sound errors in reading the Qur'an: 1. Changes in phonemes using thin (light) sounds instead of thick (heavy) sounds or vice versa. Namely: the use of the phoneme /د/ to replace the phoneme /ض/, the use of the phoneme /أ/ to replace the phoneme /ع/, the use of the phoneme /ه/ to replace the phoneme /ح/, the use of the phoneme /ك/ to replace the phoneme /ق/, the use of the phoneme /س/ to replace the phoneme /ش/,ذ/. 2. The exchange of phonemes that have close articulations. Namely: The use of the phoneme /س/ to replace the phoneme /ص/ and the use of the phoneme /س/ to replace the phoneme /ث/. 3. Words that are often heard but are wrong in pronunciation, namely: pronunciation /أنعمت/ which is read /أنعمت/. 4. The omission of phonemes that function as Mad readings. Namely: the letter /آ/.